2016
DOI: 10.1177/1073191115605613
|View full text |Cite
|
Sign up to set email alerts
|

Feigned Adjudicative Incompetence

Abstract: Psychological assessments are highly dependent on the forthrightness and sincere efforts of examinees. In particular, evaluations in forensic settings must consider whether feigning or other response styles are utilized to intentionally distort the clinical presentation. The current study examines the effectiveness of the Inventory of Legal Knowledge (ILK) at detecting feigned incompetency within a sample of jail detainees. As an ancillary goal, several scales of the Standardized Assessment of Miranda Abilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 20 publications
(32 reference statements)
2
34
2
Order By: Relevance
“…For the genuine condition (i.e., standard instructions), archival data were previously collected as part of programmatic Miranda research supported by the National Science Foundation (NSF) Law and Social Sciences Program. As summarized in the Introduction, the programmatic results have been previously reported (Rogers et al, 2016; Rogers, Robinson, & Henry, 2017; Sharf, Rogers, & Williams, 2017; Sharf, Rogers, Williams, & Drogin, 2017). For the feigning condition (i.e., simulation of impaired Miranda abilities), new data were collected from one of the previously used research sites.…”
Section: Methodsmentioning
confidence: 92%
See 3 more Smart Citations
“…For the genuine condition (i.e., standard instructions), archival data were previously collected as part of programmatic Miranda research supported by the National Science Foundation (NSF) Law and Social Sciences Program. As summarized in the Introduction, the programmatic results have been previously reported (Rogers et al, 2016; Rogers, Robinson, & Henry, 2017; Sharf, Rogers, & Williams, 2017; Sharf, Rogers, Williams, & Drogin, 2017). For the feigning condition (i.e., simulation of impaired Miranda abilities), new data were collected from one of the previously used research sites.…”
Section: Methodsmentioning
confidence: 92%
“…Rogers and his colleagues (Rogers, Henry, Sharf, Robinson, & Williams, 2017; Rogers, Robinson, & Henry, 2017) conducted two feigning investigations on two SAMA measures using adult detainees. In Rogers, Robinson, and Henry (2017), detainees simulated adjudicative incompetence on two SAMA measures: the MVS and the Miranda Quiz (MQ; Rogers, Sewell, et al, 2012). Predictably, detainees had no difficulty in feigning severe impairment on the MVS and MQ.…”
Section: Assessment Of Feigned Miranda Impairmentmentioning
confidence: 99%
See 2 more Smart Citations
“…SAMA research (Rogers, Robinson, & Henry, 2015) has demonstrated how easily adult detainees can appear to be extremely impaired with respect to their Miranda abilities. Presumably, the MRCI is no exception, especially given the transparency of its items.…”
Section: Discussionmentioning
confidence: 99%